Identification of Agroclimatic risk areas for dairy livestock systems in Valle de Ubaté y Chiquinquirá and Alto Chicamocha - Martínez, Fabio Ernesto; Castillo, Liliana; Rojas B., Edwin; Gómez-Latorre, Douglas A.; Aguilera G., Elizabeth (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2017)
In this study, the agroclimatic suitability for dairy livestock systems was determined with an “Agroclimatic suitability index (ASI)”. The index was constructed from the territorial analysis of restrictive variables such as slope, frost exposure, Bos taurus temperature and humidity index. The soil water deficit frequency was calculated with water balances, days without rain and accumulated average precipitation. The agroclimatic index identified critical areas for dairy livestock systems in the main dry periods (December to February and June to August). The results showed that in the first dry quarter, there was a larger area with agroclimatic limitations as compared to the second dry quarter. About 192,369 ha, located mainly in the Alto Chicamocha, had the lowest IAC values, indicating a lower agroclimatic suitability. Sogamoso, Corrales, Tutaza, Belen, Santa Rosa de Viterbo, Floresta, Nobsa, Sotaquira, Cerinza, Pesca, Chiquiza, Tausa, Samaca, Cucaita, Sogamoso and Firavitoba were the municipalities with the lowest agroclimatic suitability index for the two dry periods. The areas with the lowest limitations (with higher IAC values) were observed in 12% of the studied area and corresponded mainly to the municipalities of Oicata and Cuitiva in the Alto Chicamocha and Cucunuba in the Valle de Ubate and Chiquinquira.